AN ANALYSIS OF INHIBITING FACTORS AFFECTING STUDENTS’ ENGLISH- SPEAKING PERFORMANCE - Azizah, Yuniarsih; Munir, Munir; Aeni, Nur (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
English is one of the international languages, as well as the UN's official language (United Nations).  Mastering  English  will  increase  an  individual's  opportunities  to  learn  about  the world  and  compete  on  a  global  scale.  Nonetheless,  English  proficiency  among  Indonesians remains quite low. According to EF-EPI, Indonesia is in the low ability category for English proficiency, ranking 80th out of 112 countries. Then why is it like this when English has been a required subject in schools and has been taught for a long time to Indonesian students? In truth, there are inhibiting factors affecting students' English performance. In truth, there are inhibiting factors affecting students' English performance. The purpose of this research is to determine the factors that inhibit performance by focusing on data sources. specifical students from SMK-SMTI Makassar 12th grade in the 2021/2022 academic year. This study's findings revealed  ten  inhibiting  factors which  are grammar,  vocabulary,  lack  of  self-confidence, familiarity  and  feeling  toward  the  topic,  self-esteem,  interlocutor,  self-consciousness, pronunciation, shyness, and anxiety. Keywords— English-Speaking Skills, Inhibiting Factors.